2005
DOI: 10.1103/physrevlett.94.050401
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Geometric Phase for Mixed States Using Single Photon Interferometry

Abstract: Geometric phase may enable inherently fault-tolerant quantum computation. However, due to potential decoherence effects, it is important to understand how such phases arise for mixed input states. We report the first experiment to measure mixed-state geometric phases in optics, using a Mach-Zehnder interferometer, and polarization mixed states that are produced in two different ways: decohering pure states with birefringent elements; and producing a nonmaximally entangled state of two photons and tracing over … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 29 publications
1
54
1
Order By: Relevance
“…The geometric phase can be directly measured from the shift of the interference pattern. Mixed state geometric phase has been experimentally demonstrated by Du et al [12] using NMR and by Ericsson et al [13] using single photon interferometry. Du et al have experimentally demonstrated the mixed state geometric phase by measuring the relative phase change of an auxiliary spin.…”
Section: Introductionmentioning
confidence: 98%
“…The geometric phase can be directly measured from the shift of the interference pattern. Mixed state geometric phase has been experimentally demonstrated by Du et al [12] using NMR and by Ericsson et al [13] using single photon interferometry. Du et al have experimentally demonstrated the mixed state geometric phase by measuring the relative phase change of an auxiliary spin.…”
Section: Introductionmentioning
confidence: 98%
“…(i) Very recently, geometric phases for mixed states [20] have been observed in experiments by using NMR interferometry [21] as well as single photon interferometry [22]. Under a certain noisy environment, the states |χ ± (θ, ϕ) may become mixed states as…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…(22) can be expressed in terms of the concurrence of the states |χ ± (θ, ϕ) as γ ± = ∓π(1 − √ 1 − C 2 ), with C = | sin θ| being the concurrence. It is well-known that C is an invariant of entanglement for the entangled states |χ ± (θ, ϕ) , while Berry phase is related to some certain topological structures.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations